Expanding the Clinical Use of CDK4/6 Inhibitors in the Treatment of Hormone Receptor-Positive, HER2-Negative Breast Cancer from Metastatic Setting to Adjuvant Setting - Abdel-Razeq H; Sharaf B (Dove Medical Press, 2022)
Hikmat Abdel-Razeq,1,2 Baha' Sharaf1 1Department of Internal Medicine, King Hussein Cancer Center, Amman, Jordan; 2School of Medicine, The University of Jordan, Amman, JordanCorrespondence: Hikmat Abdel-Razeq, Department of Internal Medicine, King Hussein Cancer Center, Queen Rania Al Abdullah Street, P.O. Box: 1269, Amman, 11941, Jordan, Tel +962-6 5300460, Ext: 1000, Email habdelrazeq@khcc.joAbstract: More than two-thirds of patients with breast cancer present with hormone receptor (HR)-positive, human epidermal growth factor receptor-2 (HER2)-negative disease at their initial diagnosis. HR-positive breast cancer's growth depends on Cyclin D1, a direct transcriptional target of estrogen receptors (ER). The recent introduction of cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors (palbociclib, ribociclib, and abemaciclib) has revolutionized the treatment of metastatic HR-positive, HER2-negative breast cancer in both endocrine-sensitive and endocrine-resistant settings and in both pre-and post-menopausal women. Multiple large randomized clinical trials had demonstrated improvement in progression-free survival (PFS) and, more recently, in overall survival (OS). Adjuvant endocrine therapy (ET) significantly reduces the risk of recurrence and death among patients with HR-positive early-stage breast cancer (EBC). However, up to 20% of these patients will experience local, regional or distal recurrences in the first ten years. Such resistance to ET motivated researchers to try CDK4/6 inhibitors in EBC, both in adjuvant and neoadjuvant settings. While many clinical trials are still ongoing, at least one study and two meta-analyses had shown beneficial results, based on which the US Food and Drug Administration had recently approved the use of one of these agents, abemaciclib, in combination with ET for the adjuvant therapy of patients with high-risk EBC. In this paper, we review the recently published and ongoing landmark clinical trials attempting to expand the use of CDK4/6 inhibitors, in combination with ET, in the adjuvant setting of EBC.Keywords: CDK4/6 inhibitors, ribociclib, palbociclib, abemaciclib, early-stage breast cancer, adjuvant